Suffering, care, and the good life: some ethical remarks - Navarini, Claudia (Filosofia Morale/Moral Philosophy, 2024)
Pain and suffering can be seen as distinct experiences, although they show analogies and mutual influence. On a moral level, we might consider if and why a “painful life” is an overall “bad life”, or if (and why) some personal resources can be found to cope better with it and ultimately preserve the possibility of pursuing some “goods”. In this paper I will first address the two notions of pain and suffering, and then focus on the inner condition of human suffering, with the aim of identifying possible ethical and anthropological meanings. While suffering remains a challenging and undesirable situation in life, some personal goals and virtues may be compatible with it and can therefore be cultivated accordingly. Moreover, the human condition of suffering may even reveal some aspects of our identity, our deepest needs, and seemingly unrelated positive values, especially those related to our relational dimension. In conclusion, human flourishing can be sought despite the undeniable condition of suffering, and a constructive attitude towards suffering can yield significant elements such as mutual love and the joy that comes with it.